SCHOOL HEADS’ COACHING AND MENTORING COMPETENCE ON TEACHERS’ CLASSROOM MANAGEMENT, INSTRUCTIONAL DELIVERY AND RESEARCH AND INNOVATION ENGAGEMENT - Segura, Linny J. (President University, 2024)
This research study was conducted to ascertain the competency level of school heads coaching and mentoring on teachers’ classroom management, instructional delivery and research and innovation engagement. Thus, this study will serve as the basis for sustainability plan of the Deped program. The respondents of the study were the three hundred thirty-eight (338) teachers in the 3rd Congressional District, Schools Division of Iloilo. They were chosen through multi-stage sampling technique. A duly validated and pre-tested instrument was used to ascertain the level of school heads coaching and mentoring competence on teacher’s classroom management, instructional delivery and research and innovation engagement. Frequency, percentage, mean and standard deviation were utilized as descriptive statistical tools; MANOVA was used as inferential statistical tools with level of significance set at .05. The findings revealed that the level of school heads coaching and mentoring competence on teacher’s classroom management, instructional delivery, and research and innovation engagement when taken as an entire group and when classified according to age, sex, civil status, length of service and educational attainment was expert. Also, the findings revealed that there was no significant difference in the competency level of school heads coaching and mentoring on teacher’s classroom management, instructional delivery, research and innovation engagement when grouped as to age, sex, civil status and educational attainment. However, when grouped as to length of service, significant difference existed in the competency level of school heads coaching and mentoring on teacher’s classroom management, instructional delivery, research and innovation engagement.